2022
DOI: 10.56093/ijans.v92i9.110559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of lutein on laying performance and egg quality in laying hens

Abstract: Seventy Brown-Nick laying hens (39-wk old) were divided into 5 treatment groups of similar mean body weight and egg production, comprising 14 birds in each. The birds were housed in individual cages in a completely randomized design and 16:8 h light:dark photoperiod was employed. The birds were fed standard layer diets containing different levels of lutein for 6 weeks. Treatment groups included control (without lutein), 100, 200, 400 and 800 ppm lutein respectively. The results attained from this study indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
3
0
0
Order By: Relevance
“…Adding lutein from 0 to 80 ppm in the laying hen ration will produce a similar albumen index, yolk and albumen ratio, egg weight, yolk weight, and albumen weight. It is consistent with the findings that the addition of lutein to the laying hen diets had no impact on the weight of the yolk and albumen [6]. A similar output was found that egg mass and egg quality are unaffected by levels of 10, 20, 30, and 40 mg/kg of non-saponified lutein from marigold flower powder and saponified lutein from marigold flower extract [8].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Adding lutein from 0 to 80 ppm in the laying hen ration will produce a similar albumen index, yolk and albumen ratio, egg weight, yolk weight, and albumen weight. It is consistent with the findings that the addition of lutein to the laying hen diets had no impact on the weight of the yolk and albumen [6]. A similar output was found that egg mass and egg quality are unaffected by levels of 10, 20, 30, and 40 mg/kg of non-saponified lutein from marigold flower powder and saponified lutein from marigold flower extract [8].…”
Section: Resultssupporting
confidence: 90%
“…The various dietary levels of lutein from marigold extract had not been a significant effect (P>0.05) on egg weight and all egg components stored for one day. Egg weight in this study was not affected by lutein administration as was the result of the study that administration of 100 to 800 ppm lutein to laying hens aged 46 weeks resulted in the same weight in all treatments [6]. On the contrary, the addition of marigold to the diet of laying hens kept for 42 days resulted in different egg weights even though egg production tended to be the same [7].…”
Section: Resultssupporting
confidence: 48%
“…Similarly Khatun et al, 30 found no significant (P≥0.05) result for egg weight and hen day egg production. Our results are indirectly supported by the Margareta et al, 31 report that insect meal product have no significant effect on egg weight, albumin height and Haugh unit. Similar results were also observed by the report of Atteh 14 that different egg quality parameters were not affected significantly (P≥0.05) using maggot meal in layers diet.…”
Section: Discussionsupporting
confidence: 87%
“…According to [14] bioactive compounds and probiotics improved the health status of the poultry. This research is in line with the statement of Salari et al who stated that feed additive lavender essence which has the bioactive compound did not affect external egg quality [15]. The outcomes of the current study do not align with the previous finding [16], who documented that the supplementation of peppermint leaves at 5-10 g/kg demonstrated improvements in egg weight and shape index.…”
Section: Resultssupporting
confidence: 70%